Manipulating the light intensity by magnetophotonic metasurfaces - Musorin, Alexander I. (2020)
We study numerically the possibility of controlling light properties by means of an external magnetic field. Considerable changes in the shape, value, and spectral position of the magneto-optical response are demonstrated in Voigt geometry for the transmitted light depending on the parameters of the magnetophotonic metasurface made up of nickel/silicon nanoparticles. The spectral overlapping of the fundamental magnetic and electric dipole Mie resonances leads to interference with a strong modification of phase relations, which manifests itself through an enhanced magneto-optical signal.